Smoke-Free Campus Awareness Scale: A Validity and Reliability Study - Dereli, Feyza; Tekindal, Mustafa Agah; Tekindal, Melike (Addicta: The Turkish Journal on Addictions, 2023)
Our team conducted this study to develop the Smoke-Free Campus Awareness Scale and to test the validity and reliability of this scale. The study took place between November 2022 and January 2023 with individuals studying and working at a university after obtaining institutional permission and ethics committee approval. The study sample comprised 211 participants. We collected the data using the questionnaire prepared by the researchers and the Smoke-Free Campus Awareness Scale, which was content validated. Our team evaluated the scale’s validity and reliability via IBM Statistical Package for the Social Sciences 25 (IBM SPSS Corp.; Armonk, NY, USA) and AMOS (Analysis of Moment Structures) 25 programs. Kendall’s analysis and Barlett’s test of sphericity (p < .001) were significant in the study. To verify the construct validity of the Smoke-Free Campus Awareness Scale, we applied the confirmatory factor analysis and the exploratory factor analysis. After the Smoke-Free Campus Awareness Scale’s exploratory factor analysis, we concluded that there was a single factor for 11 items. In the fit indices model, it was determined that the scale was compatible satisfactorily. The scale’s Cronbach’s alpha coefficient was 0.898. Test–retest reliability analysis was found significant. We determined that the Smoke-Free Campus Awareness Scale is a valid and reliable measurement tool.
Keywords: Reliability; scale development; smoke-free campus; smoking; validity